Determinants of Born Global Success in Food MSMEs in East Java : (A Case Study of Export-Oriented Processed Food MSMEs) - Aisy Fiklil Nafisah; Sudarmiatin Sudarmiatin; Heri Pratikto (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the determinants of success of PT Makmur Susanti Group, a processed food MSME in Tulungagung, East Java, in achieving “Born Global” status by bypassing the traditional incremental internationalization process and penetrating global markets within only 2.5 years. The research employed a qualitative approach using a single case study method. Data were collected through semi-structured in-depth interviews with the owner as the key informant, participatory observation, and documentation, and were analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the company’s rapid internationalization was supported by three main factors, namely visionary managerial capability reflected in entrepreneurial alertness, continuous product innovation through selective raw material use and flavor localization, and the optimal utilization of digital ecosystems such as B2B platforms and Alibaba. In addition, the study identified a “symbiotic” business model involving export aggregators to serve diaspora niche markets, which challenges the conventional assumption that Born Global firms must independently manage international logistics. Furthermore, the owner’s legal background became a strategic advantage in addressing complex halal regulations and international certification requirements. This research contributes a new perspective on the phenomenon of “non-intentional” Born Global firms and highlights the importance of legal-formal competence for MSMEs, while also providing practical insights for regional MSMEs in integrating local comparative advantages with global competitive standards.